Flexible and Highly Sensitive Pressure Sensors Based on Bionic Hierarchical Structures. (19th January 2017) - Jian, Muqiang; Xia, Kailun; Wang, Qi; Yin, Zhe; Wang, Huimin; Wang, Chunya; Xie, Huanhuan; Zhang, Mingchao; Zhang, Yingying
Abstract : The rational design of high‐performance flexible pressure sensors attracts attention because of the potential applications in wearable electronics and human–machine interfacing. For practical applications, pressure sensors with high sensitivity and low detection limit are desired. Here, ta simple process to fabricate high‐performance pressure sensors based on biomimetic hierarchical structures and highly conductive active membranes is presented. Aligned carbon nanotubes/graphene (ACNT/G) is used as the active material and microstructured polydimethylsiloxane (m‐PDMS) molded from natural leaves is used as the flexible matrix. The highly conductive ACNT/G films with unique coalescent structures, which are directly grown using chemical vapor deposition, can be conformably coated on the m‐PDMS films with hierarchical protuberances. Flexible ACNT/G pressure sensors are then constructed by putting two ACNT/G/PDMS films face to face with the orientation of the ACNTs in the two films perpendicular to each other. Due to the unique hierarchical structures of both the ACNT/G and m‐PDMS films, the obtained pressure sensors demonstrate high sensitivity (19.8 kPa −1, <0.3 kPa), low detection limit (0.6 Pa), fast response time (<16.7 ms), low operating voltage (0.03 V), and excellent stability for more than 35 000 loading–unloading cycles, thus promising potential applications in wearable electronics. Abstract : A flexible, highly sensitive, and low operating voltage pressure sensor is fabricated based on carbon nanotube/graphene hybrid films and hierarchical microstructured polydimethylsiloxane films molded from natural leaves. The sensor has high sensitivity (19.8 kPa −1, <0.3 kPa), a low detection limit (0.6 Pa), fast response time (<16.7 ms), low operating voltage (0.03 V), and excellent stability for over 35 000 cycles.